Pengembangan Potensi Gulma Kirinyuh Dan Limbah Pertanian Sebagai Pupuk Organik Alternatif Di Nagari Palaluar Kecamatan Koto Vii Kabupaten Sijunjung Sumatera Barat - Syofiani, Riza; Putri, Santi Diana (Agrium, 2019)
Nagari Palaluar, Koto VII Subdistrict, Sijunjung Regency has an area of 5,47.17 ha. . The farmer groups in Palaluar Nagari who are partners are the Gelugur Jaya Farmers Group and the Minang Farmers Group. The dominant farming effort was cultivated by the Gelugur Jaya farmer group, namely rice. In rice cultivation, farming communities in this group every planting season always use artificial fertilizers. Even though rice harvested straw can be reused as an alternative source of organic fertilizer. Most of the agricultural waste, namely rice straw, is simply burned so that it can increase global warming. There are quite a lot of weeds in empty land and on the roadside in the Gelugur Jaya farmer group area. However, farmers have never used it as a source of organic material. Then the Minang farmer group built, the dominant farming business was rice and corn and cocoa plants. Cocoa plants produce a lot of waste, that is, cocoa skin waste is left piling around the land. Therefore it is necessary to process agricultural wastes. The objectives of this PKM program are (1) to increase the knowledge of partner group farming communities about the potential for sugar weeds and agricultural waste as alternative organic fertilizers in reducing the use of artificial fertilizers (2) provide examples of the application of rice cultivation techniques to the use of alternative organic fertilizers, namely weeds and agricultural waste to reduce the application of artificial fertilizers and increase the yield of rice crops. The method of carrying out activities is carried out by lecture, question and answer, demonstration, training (practice), assignment, mentoring and evaluation. The results expected from the implementation of the program are: (1) farmers' knowledge will increase about the importance of making and the potential of sugar weeds and agricultural waste as a source of alternative organic fertilizers to reduce the application of artificial fertilizers and increase rice production. (2) the farming community of the partner group is willing and able to imitate the application of rice cultivation techniques by utilizing sugar weeds and agricultural waste as an alternative organic fertilizer. Keywords : kirinyuh, agricultural waste, organic fertilizer, rice production